SEMANTICS AND TRANSLATABILITY OF WINGED EXPRESSIONS IN THE RUSSIAN AND ENGLISH LANGUAGES - Dilzoda Mirzaeva, PhD (Western European Studies, 2025)
This article examines the semantic features and translatability of winged expressions— idiomatic phrases or fixed expressions with cultural or historical significance—in Russian and English languages. It discusses the origin, classification, and semantic fields of such expressions and explores the translation challenges they pose. By comparing examples from both languages, this study highlights the importance of cultural context in achieving accurate translation and proposes strategies for effective equivalence.
Keywords: Winged expressions; idioms; semantics